Matrix Variate Pareto Distribution of the Second Kind. (25th September 2012) - Nagar, Daya K.; Joshi, Lata; Gupta, Arjun K.
Abstract : We generalize the univariate Pareto distribution of the second kind to the matrix case and give its derivation using matrix variate gamma distribution. We study several properties such as cumulative distribution function, marginal distribution of submatrix, triangular factorization, moment generating function, and expected values of the Pareto matrix. Some of these results are expressed in terms of special functions of matrix arguments, zonal, and invariant polynomials.